Comparison of the Efficiency of GlobalfilerTM IQC PCR Amplification Kit and Powerplex® Fusion 6C System with Half-Volume Reactions for Forensic Trace DNA Testing - Nattawoot Saokaew; Kewalee Junpan; Wawkan Duangshatome; Duangnate Pipatsatitpong; Ratchaneewan Aunpad (Institute of Medico-legal Publications Pvt Ltd, 2022)
Two major challenges in daily and routinely forensic genetics test are samples with low or very low quantitiesof DNA and high cost of processing. To overcome these obstacles, a reduction in reaction volume to half wouldoffer a substantial benefit, but even so it should provide complete genetic profiles without conceding the qualityof the results. The aim of this study is to test the robustness of two commercially available kits, GlobalFilerTMIQC PCR Amplification Kit (GF-IQC) and PowerPlex® Fusion 6C System (P-6C), with half volume reaction inaccordance with SGWDAM guidelines. GF-IQC showed minimum and stochastic threshold of 45 and 610 RFU,while P-6C demonstrated 60 and 670 RFU of those values respectively. The P-6C can tolerate to many inhibitorsincluding melanin, hematin, and humic acid. Both kits showed the same performance on case work profiling andthe sensitivity of allele detection of P-6C was not significantly different from that of GF-IQC (p=0.144). The resultsof this study demonstrated that GF-IQC and P-6C with half volume reaction can produce good quality profiles andcould be applied for forensic DNA examination.